Surprised by doubt : how disillusionment can invite us into a deeper faith - Chatraw, Josh; Carson, Jack, 1995- (Grand Rapids, MI. Brazos Press, 2023)
"Building on the metaphor of Christianity as a house, two apologetics scholars invite doubters to leave the confines of late-modern evangelicalism for a deeper, more orthodox faith"--
Includes bibliographical references.
Keywords: Faith; Belief and doubt